2022
DOI: 10.1002/ceat.202100515
|View full text |Cite
|
Sign up to set email alerts
|

Applicability of Deep Eutectic Solvents in Oil and Gas Processing Fields for CO2 Control

Abstract: Anthropogenic greenhouse gas emissions, particularly CO 2 emissions, have grown substantially, posing environmental challenges that affect mankind and ecosystems. As a possible consequence, carbon capture and storage is a viable solution to this worldwide problem. However, some aqueous solvents have been applied to capture greenhouse gases, though they are not environmentally benign. Deep eutectic solvents (DESs) emerged as a unique choice according to research into greener solvents for this activity. The appl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 92 publications
0
4
0
Order By: Relevance
“…Recently, gas hydrate has been nominated as a medium for CO 2 capturing, mostly from flue gas as a post-combustion CO 2 capturing scenario [82][83][84]. Hydrate-based separation is attracting attention as a new capturing technology due to its lower energy requirement compared to conventional capturing technology [85,86]. Furthermore, this technology uses water as the main chemical with a small portion of additives as a promoter [87,88].…”
Section: Gas Hydrate-based Technology For Separation Of Comentioning
confidence: 99%
“…Recently, gas hydrate has been nominated as a medium for CO 2 capturing, mostly from flue gas as a post-combustion CO 2 capturing scenario [82][83][84]. Hydrate-based separation is attracting attention as a new capturing technology due to its lower energy requirement compared to conventional capturing technology [85,86]. Furthermore, this technology uses water as the main chemical with a small portion of additives as a promoter [87,88].…”
Section: Gas Hydrate-based Technology For Separation Of Comentioning
confidence: 99%
“…Carbon dioxide absorption in DESs has been extensively studied in the past decade. , Previously, we have investigated the capacity of CO 2 absorption and associated mechanism for a series of anion-functionalized protic ILs, i.e., [DBUH]­[X] . We found that the basicity of comprising anion (X – ) of the IL dictates the maximum absorption capacity as well as kinetic and mechanism.…”
Section: Resultsmentioning
confidence: 99%
“…20 For example, in the petrochemical and natural gas sectors, DESs have better properties than other traditional solvents. 21 In addition, DESs have a wide range of applications in the capture of gases such as CO 2 , H 2 S, SO 2 , etc. 22−30 Especially in CO 2 capture, DESs have higher absorption, lower price, lower toxicity, and better renewability than the other solvents.…”
Section: Introductionmentioning
confidence: 99%
“…Because DESs have many advantages such as low vapor pressure, high thermal stability, adjustable structure, degradability, low toxicity, low cost, simple synthesis, etc., , they are widely used in chemical synthesis, material preparation, biological conversion, and other fields . For example, in the petrochemical and natural gas sectors, DESs have better properties than other traditional solvents . In addition, DESs have a wide range of applications in the capture of gases such as CO 2 , H 2 S, SO 2 , etc. Especially in CO 2 capture, DESs have higher absorption, lower price, lower toxicity, and better renewability than the other solvents.…”
Section: Introductionmentioning
confidence: 99%